2019
DOI: 10.1097/hjh.0000000000001916
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hypertension on retinal capillary microvasculature using optical coherence tomographic angiography

Abstract: In adults with treated systemic hypertension, retinal capillary density reduced with higher BP and poorer eGFR. These findings highlight the potential role of OCT-A to study early microvascular changes because of systemic hypertension.This is an open access article distributed under the terms of the Creative Commons Attribution-Non Commercial-No Derivatives License 4.0 (CCBY-NC-ND), where it is permissible to download and share the work provided it is properly cited. The work cannot be changed in any way or us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
147
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(161 citation statements)
references
References 62 publications
9
147
2
3
Order By: Relevance
“…A study of Asian patients with hypertension found that those with poor BP control (assessed by 24-hour ambulatory monitoring) had a lower deep capillary plexus vessel density than did those with optimal BP control. 110 These groups were well matched in terms of age, sex, CVD risk factors, and renal function (mean eGFR w90 ml/min per 1.73 m 2 ), but the poorly controlled group had higher microalbuminuria. 110 In adjusted analyses, suboptimal BP control, increasing BP, and worsening eGFR were associated with worse capillary rarefaction.…”
Section: Oct Angiographymentioning
confidence: 86%
See 3 more Smart Citations
“…A study of Asian patients with hypertension found that those with poor BP control (assessed by 24-hour ambulatory monitoring) had a lower deep capillary plexus vessel density than did those with optimal BP control. 110 These groups were well matched in terms of age, sex, CVD risk factors, and renal function (mean eGFR w90 ml/min per 1.73 m 2 ), but the poorly controlled group had higher microalbuminuria. 110 In adjusted analyses, suboptimal BP control, increasing BP, and worsening eGFR were associated with worse capillary rarefaction.…”
Section: Oct Angiographymentioning
confidence: 86%
“…110 These groups were well matched in terms of age, sex, CVD risk factors, and renal function (mean eGFR w90 ml/min per 1.73 m 2 ), but the poorly controlled group had higher microalbuminuria. 110 In adjusted analyses, suboptimal BP control, increasing BP, and worsening eGFR were associated with worse capillary rarefaction. 110 An Italian study extended these findings by using OCT-A in 120 hypertensive patients with and without CKD to report a lower vessel density in both superficial and deep capillary plexuses in those with CKD.…”
Section: Oct Angiographymentioning
confidence: 86%
See 2 more Smart Citations
“…Prior studies showed that both ACEI/ARB and calcium channel blockers may improve the retinal arteriolar narrowing and capillary rarefaction in hypertensive patients . The benefit of anti‐hypertensive drugs may have resulted either from better‐controlled BP or from other pharmacological effects independent of the BP lowering effect. For an example, a localized RAS had been found within the eye, such as in retinal microvasculature, Müller cells, and ganglion cells .…”
Section: Discussionmentioning
confidence: 99%